TRANSPORTATION DESIGN OF ART AND CULTURE CENTER BUILDING OF BANDUNG - Thirafi, Muhammad
Art and Culture Center Building of Bandung consists of two buildings, each of which has five floors (two floors form a basement) and central park with skywalk. Each building has a planned theater can accommodate 1000 and 500 spectators. On one of the building there is also an amphitheater for performances which are parade along the skywalk. On one of the building there is also an amphitheater for performances which are parade along the skywalk. The building is planned to be built at the junction between Jl. Laswi and Jl. Sukabumi. With the construction of this building, then planning against the transport system needs to be done. In the process of designing, the main thing to do is an analysis of the number of vehicles that will come, whether it be parked or not. In analyzing the number of vehicles that will be parked, the parking needs analysis unit of parking spaces in the building has a typical function reference and attendance. Then designed the pattern produces 118 parking slot parking lot and 150 motor parking slot. After the designed parking then designing pavement on access roads. Designing pavement will makes 2 pavement design, design of flexible pavement and design of rigid pavement. The two are then compared through the lifecycle cost analysis. Selected pavement is rigid pavement that produce smaller cost based on lifecycle cost analysis with total thickness of pavement is 345 mm. After that, designing circulation of vehicles on the access roads and basement design including number of counters required parking. The number of counters used in the parking lot entrance are 2 counters for car and truck, and 1 for motorcyle which produces the average length of a queue is 0,018 car and 0,024 motorcycle. The number of counters used in the parking lot entrance are 2 counters for car, 1 for motorcyle and 1 for truck which produces the average length of a queue are 0,05 car and 0,209 motorcycle.